Biomass partitioning in response to intraspecific competition depends on nutrients and species characteristics: A study of 43 plant species. (15th March 2021) - Rehling, Finn; Sandner, Tobias M.; Matthies, Diethart
Abstract: Competition simultaneously limits the availability of above‐ and below‐ground resources for plants. How plants respond to density with changes in patterns of biomass allocation is poorly understood. Previous studies had inconsistent results, but emphasised increased biomass allocation to stems in response to density. However, the response of plants to density may depend on environmental conditions and on characteristics of the species. We grew 43 herbaceous plant species at three densities (1, 8 and 64 individuals per pot) and two nutrient levels in a common garden and measured biomass allocation to roots (RMF), leaves (LMF) and stems (SMF), and specific root (SRL) and stem length (SSL). The species differed in functional group (grasses, forbs and legumes), life span and realised niche with respect to nutrients (Ellenberg's nutrient indicator value). Intraspecific competition and self‐thinning increased with nutrient supply. Overall, plants increased their RMF with density independent of nutrient level, indicating that competition was mainly for below‐ground resources. However, characteristics of the species influenced their responses to density and nutrients in terms of biomass allocation, SRL and SSL. At high densities, legumes were more productive than the other functional groups and hardly changed their allocation patterns, suggesting that they were less nutrient limited due to their mutualism with nitrogen‐fixing rhizobia. The SRL of perennials was lower, and their RMF was higher and increased more strongly in response to density than that of annuals, which could be interpreted as mechanisms to increase survival. The realised niche of species with respect to nutrients influenced the response to density and nutrients in terms of SMF, LMF, SRL and SSL in line with adaptations to both nutrient availability and competition for light in the typical habitats. Synthesis . We found that intraspecific competition was mainly for below‐ground resources, which may be typical for many species growing in moderately nutrient‐rich but high‐light habitats. Our results show that growth conditions, species characteristics and their interactions influence patterns of biomass allocation and plant morphology. Abstract : In a study of 43 plant species, the most consistent response to density was an increase in the proportion of biomass allocated to roots, suggesting that intraspecific competition was mainly for below‐ground resources. Our results further show that growth conditions, species characteristics and their interactions influence patterns of biomass allocation and plant morphology.